Population-Based Prevalence of Intellectual Disability and Autism Spectrum Disorders in Western Australia: A Comparison With Previous Estimates. Issue 21 (May 2016) - Bourke, Jenny; de Klerk, Nick; Smith, Timothy; Leonard, Helen
Abstract : Abstract: To investigate the prevalence of intellectual disability (ID) and/or autism spectrum disorders (ASDs) in Western Australia (WA). A cohort of children born from 1983 to 2010 in WA with an ID and/or ASD were identified using the population-based IDEA (Intellectual Disability Exploring Answers) database, which ascertains cases through the Disability Services Commission (DSC) as well as education sources. Information on race, gender, mother's residence at birth and deaths was obtained through linkage to the Midwives Notification System and the Mortality Register. Diagnostic information on the cause of ID was obtained through review of medical records where available and children were classified as biomedical cause, ASD, or unknown cause. An overall prevalence of ID of 17.0/1000 livebirths (95% CI: 16.7, 17.4) showed an increase from the 10-year previous prevalence of 14.3/1000. The prevalence for mild or moderate ID was 15.0 (95% CI: 14.6, 15.3), severe ID was 1.2 (95% CI: 1.1, 1.3), and unknown level of ID was 0.9 (95% CI: 0.8, 1.0)/1000 livebirths. The prevalence for Aboriginal children was 39.0/1000 compared with 15.7/1000 for non-Aboriginal children, giving a prevalence ratio of 2.5 (95% CI: 2.4, 2.6). Prevalence of all ASD was 5.1/1000 of which 3.8/1000 had ASD and ID. The prevalence of ID has risen in WA over the last 10 years with most of this increase due to mild or moderate ID. Whilst the prevalence of ASD has also increased over this time this does not fully explain the observed increase. Aboriginal children are at a 2.5-fold risk of ID but are less likely to be accessing disability services.